1982
DOI: 10.3109/13813458209103817
|View full text |Cite
|
Sign up to set email alerts
|

The apparent buffer value of human blood for CO2as a function of temperature

Abstract: The influence of temperature on the acid-base status of normal human deoxygenated whole blood was studied in open systems (variable total CO2 content). (1) When the temperature was raised from 26 degrees C to 42 degrees C, the apparent buffering value of deoxygenated whole blood for CO2 increased by 7% of its value at 26 degrees C; this increase was not statistically significant. (2) Comparing the present data with those obtained previously from oxygenated whole blood in the same temperature range (Castaing & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The present study is about the investigation of perceived organisational politics and perceived responsibility which plays the role of mediators among the D.T.P.s and C.W.B. However, Stone- Romero and Rosopa (2008) argue that authors should not claim that the studied model is the only model consistent with the results when they use S.E.M. in the non-experimental study.…”
Section: Limitations and Further Researchmentioning
confidence: 88%
See 1 more Smart Citation
“…The present study is about the investigation of perceived organisational politics and perceived responsibility which plays the role of mediators among the D.T.P.s and C.W.B. However, Stone- Romero and Rosopa (2008) argue that authors should not claim that the studied model is the only model consistent with the results when they use S.E.M. in the non-experimental study.…”
Section: Limitations and Further Researchmentioning
confidence: 88%
“…Boddy (2010) argues that a sound control system and public scrutiny, a standard approach in the public sector, may act as a barrier for the D.T.P.s in the organisation. Empirical studies have revealed that perceived accountability is an integral part of ethical behaviour (Steinbauer et al, 2014). D.T.P.s are more sensitive to conventional norms and behaviour.…”
Section: The Mediating Role Of Perceived Accountability In the Associmentioning
confidence: 99%